The environmental pollution by corporate criminal action phenomenon - Hartanto (PHINISI, 2023)
The problem of environmental pollution is increasingly in the spotlight and globalized. The systemadopted in the criminal law of environmental pollution is a system of criminal responsibility basedon mistakes. Corporate crime can emerge as economic development advances. Corporate crime isnot new, but something that has happened frequently and has changed from time to time. Currently,corporations are included in the category of legal subjects so that they can be subject to criminaland civil sanctions. The doctrinal legal research used has the purpose of analyzing environmentalregulations related to corporations that pollute. UU no. 32/2009 Environmental Protection andManagement as a legal umbrella mentions the unitary environment of space with all objects, styles,circumstances, and organisms, including humans and their behavior that affect nature itself,survival, livelihood and welfare of humans and other living creatures. Loss of environmentalpollution is not only in one area but can spread to the surrounding area with a fantastic total lossvalue, this requires government firmness, especially in Indonesia which on the one hand tries topromote the economy and investment, but on the other hand requires legal instruments to maintainenvironment for sustainable development.